6th International Munich Chassis Symposium 2015 chassis.tech plus - Pfeffer, Peter (Proceedings, 2015)
Connectivity has arrived in the vehicle - whether it is in-car internet or car-to-car communication. For the chassis too, the connected car is increasingly becoming a driver of innovation. Predictive and intelligent chassis systems and automated driving are just some of the topics being addressed. In addition to enhancing driving comfort and safety, interconnecting the powertrain with the chassis can also provide new functions, not only in cars but also in commercial vehicles. What is more, modularization, electrification of the powertrain, intelligent development methods and efforts to reduce fuel consumption are also driving innovations in chassis systems. Contents Consumer protection and methods.- New chassis systems.- Active chassis systems.- Energy efficiency, safety, and resources.- Driver assistance systems.- Development process.- Vehicle lateral dynamics.- Steering technology.- Test bench methods.- Environmental aspects and future technologies.- Control and simulation.- Road surface, tire, and wheel interaction.- Simulation.- Ride comfort and testing.- Driving simulation and testing.- Brake technology.- Design and testing. Target audiences Automotive engineers and chassis specialists as well as students looking for state-of-the-art information regarding their field of activity - Lecturers and instructors at universities and universities of applied sciences with the main subject automotive engineering - Experts, researchers and development engineers of the automotive and the supplying industry Publisher ATZ live stands for top quality and a high level of specialist information and is part of the worldwide specialist scientific publishing group Springer Science + Business Media. Partner TÜV SÜD is an international leading technical service organisation catering to the Industry, Mobility and Certification Segment.